2004
DOI: 10.1097/00024382-200405000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic Regulation of Cell Function and Possible Clinical Applications

Abstract: Inflammation and immunosuppression can cause acute respiratory distress syndrome, multiple organ failure, and sepsis, all of which are lethal posttraumatic complications in trauma patients. Prevention of the inflammation and immunosuppression has been a main focus of trauma researcher for many years. Recently, hypertonic resuscitation has attracted attention as a possible therapeutic approach to counteract such deleterious immune responses in trauma patients. We have begun to understand how hypertonic fluids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 152 publications
1
52
0
3
Order By: Relevance
“…Multiple injuries and major hemorrhage induce marked dysregulation of the systemic immune response, end organ damage, and death (33)(34)(35)(36)(37)(38). In patients with multiple injuries who are at risk for infectious complications, outcome is believed to be determined by the interrelationship of various inflamma- Genomic and nongenomic effects of estrogen.…”
Section: Sex Dichotomy In Trauma Outcomementioning
confidence: 99%
“…Multiple injuries and major hemorrhage induce marked dysregulation of the systemic immune response, end organ damage, and death (33)(34)(35)(36)(37)(38). In patients with multiple injuries who are at risk for infectious complications, outcome is believed to be determined by the interrelationship of various inflamma- Genomic and nongenomic effects of estrogen.…”
Section: Sex Dichotomy In Trauma Outcomementioning
confidence: 99%
“…The impairment in host defense following trauma could result from a defect in cellmediated immune responses (3,4) and impaired microbicidal activity by cells of the innate immune system. A number of studies have demonstrated that trauma-hemorrhage (T-H) 3 induces a marked alteration of many immune functions, including T cell activation, proliferation and cytokine release, macrophage Ag presentation function, and cytokine release (5)(6)(7)(8)(9). Furthermore, our previous studies have shown that following hemorrhage, splenic macrophage, peritoneal macrophage, and Kupffer cell Ag-presenting capacity are depressed, and this depression is associated with decreased MHC class II expression (10,11).…”
Section: T Is Well Known That Traumatic Injury-induced Immunosup-mentioning
confidence: 99%
“…Many studies have demonstrated that trauma-hemorrhage induces marked alterations in various immune functions (Meldrum et al, 1997;Murphy et al, 2005;Murphy et al, 2004;Noel et al, 2005;Shukla et al, 2004;Zuckerbraun et al, 2005). Severe hemorrhage followed by adequate resuscitation with blood and crystalloid solutions is known to produce depression of immune system, such as lymphocyte functions and macrophage functions (Chaudry and Ayala, 1993).…”
Section: Introductionmentioning
confidence: 99%